Investigating the impact of NHS based ovarian cancer screening - Nicholson, S. M. (Cranfield University, 2010)
the UK ovarian cancer is the fifth most common cancer in females and after uterine cancer, the second most common gynaecological cancer. There were 6,596 new cases diagnosed in the UK in 2006. The majority of women who develop ovarian cancer have few symptoms until the cancer has spread. A systematic review of published literature was performed to include randomised control trials, case control or cohort studies. It is apparent from the literature on ovarian cancer screening that internationally extensive research is performed however, there is lack of consensus on who to offer screening to, and the most efficacious way of offering it. Annual screening was found to be inadequate for early cancer detection as several studies report advanced stage disease or found that women were developing symptoms in the interim period of screening visits. The retrospective studies performed at Milton Keynes Hospital demonstrated that ovarian cancer affects a wide age range with many women having no family history of ovarian or breast cancer. Many cases were found to have early stage ovarian cancer however, the largest group of women were found to have extensive metastatic disease at time of diagnosis. 80% of cases reviewed experienced abdominal or pelvic pains often with distension. Five patients were found to have a CA125 value in the normal range, one of which had advanced disease, indicating the limitations of this biomarker. The impact and costs associated with screening in the NHS setting vary considerably with inclusion criteria used. The UK National Screening Committee will have to decide once the findings of UKCTOCS are published in 2010/11 as to the cost benefit of offering NHS based ovarian cancer screening. An annual cost of at least £1.3 million should be expected per NHS trust, in addition to individual trusts needs for equipment, staff and additional facilities required to offer such screening.